Architecting a priority-based dynamic media access control mechanism in Wireless Network-on-Chip. (October 2021) - Ouyang, Yiming; Sun, Chenglong; Jia, Boyuan; Wang, Qi; Liang, Huaguo
Abstract: Wireless Network-on-Chip (WiNoC) are being examined for parallel applications to improve the performances by reducing multi-hop latency. Wireless nodes handle massive data transmission assignment, the data bandwidth and energy efficiency of the WiNoC architecture can be improved by establishing wireless links to respond to dynamically changing traffic patterns. Among them, the wireless token mechanism is widely used, since it would take little additional hardware overhead and simple operation process. However, the traditional wireless token mechanism is a time-division-multiplexed fair strategy, and cannot well cope with non-uniform traffic patterns. In this paper, a priority-based dynamic media access control (MAC) mechanism in wireless network-on-chip is architected by redefining MAC mechanism, which aims to make wireless MAC protocols more suitable for non-uniform traffic patterns. Experimental results show that the proposed scheme in this paper guarantees the network performance equivalent to the traditional token mechanism in random traffic mode, and the network throughput is increased by 14%–15% in the hotspot mode. Compared with the traditional token mechanism, the average packet delay is greatly reduced before the saturation point with little extra hardware overhead introduced simultaneously.